Synthesis of 8-HEPE and 10-HDoHE in both (R)- and (S)-Forms via Wittig Reactions with COOH-Ylides - Suganuma, Yuta; Saito, Shun; Kobayashi, Yuichi (Synlett, 2019)
Wittig reactions using carboxy (CO2H) ylides derived from a carboxylic phosphonium salt and NaN(TMS)2 (NaHMDS) in a 1:1 ratio were applied to the synthesis of 8-HEPE and 10-HDoHE, which are metabolites of eicosapentaenoic acid and docosahexaenoic acid, respectively. The attempted Wittig reaction of 3-(TBS-oxy)pentadeca-4E,6Z,9Z,12Z-tetraenal with the carboxy ylide (2 equiv) derived from Br– Ph3P+(CH2)4CO2H and NaHMDS (1:1) competed with the elimination of the TBS-oxy group at C3 to give a mixture of the Wittig product and the elimination product in 45–50% and 30–40% yields, respectively. The elimination was suppressed completely by using three equiv of the carboxy ylides in THF/HMPA (7–8:1), and the subsequent desilylation gave 8-HEPE in (R)- and (S)-forms. Similarly, both enantiomers of 10-HDoHE were synthesized.
Keywords: lipoxygenase metabolite; 10-HDoHE; 8-HEPE; Wittig reaction; carboxy phosphonium salt